Progressive Study on the Non-thermal Effects of Magnetic Field Therapy in Oncology - Xu, Aoshu; Wang, Qian; Lv, Xin; Lin, Tingting (Frontiers in Oncology, 2021)
Cancer is one of the most common causes of death worldwide. Although the existing therapies have made great progress and significantly improved the prognosis of patients, it is undeniable that these treatment measures still remain some serious side effects. In this context, a new treatment method is needed to address these shortcomings. In recent years, the magnetic fields have been proposed as a novel treatment method with the advantages of less side effects, high efficiency, wide applications and low costs without forming scars. Previous studies showed that static magnetic fields (SMFs) and low-frequency electromagnetic fields (LF-MFs, frequency below 300Hz) exert anti-tumor function independent of thermal effects. Magnetic fields (MFs) could inhibit cell growth and proliferation, induce cell cycle arrest, apoptosis, autophagy, differentiation and regulate the immune system, and suppress angiogenesis, metastasis via various signaling pathways. In addition, they are effective in combination therapies, MFs not only promote the absorption of chemotherapy drugs by producing small holes on the surface of cell membrane, but also enhance the inhibitory effects by regulating apoptosis and cell cycle related proteins. Meanwhile, MF can be used as drug delivery systems to target magnetic nanoparticles to tumors. This review aims to summarize and analyze the current knowledge of the pre-clinical studies of anti-tumor effects, the underlying mechanisms and discuss the prospects of the application of MF therapy in cancer prevention and treatment.